PERANCANGAN TATA LETAK PADA AREA WAREHOUSE PT SIMATELEX MANUFACTORY BATAM - Andriansyah; Asmarawati, Citra (Computer Science and Industrial Engineering, 2022)
Simatelex establishes a new factory in Batam, Indonesia. With these conditions, the current problems faced are the accumulation of materials and the accumulation of finished goods that exceed the capacity of the land and the placement of materials that are still messy or mixed. To improve the layout of the material in the warehouse area, this study uses the Activity Relationship Chart and the CRAFT Algorithm method which will produce a form of production facility layout design that regulates production material traffic so that it runs smoothly and minimizes the total cost of material handling. The results show that this method can redesign the layout of the warehouse area to be better than the previous layout at PT Simatelex manufactory batam. Where from the 5 options selected are options B and C, because the flow of the production process has been regulated in accordance with the manufacture of PM3 PRODUCT so that it can reduce the total distance of material handling transfers and can save material handling costs so that layout improvements in the placement of raw parts for the work process are needed. by PT Simatelex Manufactory Batam to reduce transfer distances and reduce the level of material mixing.